Shiny Dashboard with MongoDB Database Management - Mugilan a/l Ravntheran, Mugilan (IRC, 2020)
In concise, my project work is to develop a dashboard system using the R Analytics with a database management. The software used to develop the dashboard will be the R Studio which is a reliable software utility when it comes to building an online web applications such as dashboard and it also offers a multi various kind of features which is pre-built in the development tools system which is useful when it comes to build a dashboard system. The influence on R programming language had gained my interest to do something utilizing this particular programming language so I came up with the idea of developing a dashboard for the healthcare area/sector which will be primarily used to measure the KPIs of the medical organization. As the main objective is to develop an overall well-performing dashboard system which can be used in the healthcare area sectors. When we talk about KPIs, it is really an interesting topic because as we already knw, KPIs are very crucial and need to be taken into consideration when it comes to organizational excellence. Each and every organizations already have their relevant KPIs which will also predict their future business processes using the KPIs and healthcare metrics. The sample dataset needs to be relevant to my project so more data sources/ web platforms need to be accessed for sample dataset with right number of measurements which will somehow ease the process of identifying the KPIs. Next, the database management is most probably will be done using the MongoDB NoSQL which will be connected to this dashboard system which is yet to be developed. Again , changes in methodologies will occur as per the recommendations from the project supervisor in future.